ТУРИЗМНИ РИВОЖЛАНТИРИШДА МУЛОҚОТ МАДАНИЯТИ - Xolmuradova, shahnoza (FILOLOGIYA UFQLARI JURNALI, 2021)
This article highlights the importance and problems of the culture of communication in the development of tourism, and the prospects for the further development of tourism in our country are scientifically substantiated.